Iowa RBA, July 25-29, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Three emails of Iowa RBA updates for July 25, 27, 29, 1999. Highlights of the updates include sightings of a Little Blue Heron, Least Terns and a Buff-breasted Sandpiper. Epson - sheet feed/flatbed